Early Meissen Coffee and Tea Sets in the Collections of the Museum of Warsaw – Introductory Remarks - Ewelina Więcek-Bonowska (Fasciculi Archaeologiae Historicae, 2024)
The 18th century was a period of intensive cultural changes in Europe. For Poland, this was the beginning of the reign of a new dynasty – the Wettins. As a lover of art and collector of Far Eastern porcelain, the first king of this dynasty, August II, led to the establishment of the first European porcelain factory in 1710 in Saxon Meissen. Early Meissen products include coffee and tea sets as an expression of socio-cultural changes related to changes in culinary habits. The work aims to present early Meissen products as evidence of the rapid development of consumption of new beverages, as well as to announce the interesting phenomenon of the occurrence of a relatively large number of vessels from early manufacturing activities in Warsaw, which will be confronted with analogies from other cities in present-day Poland.